Integrated weed management in cauliflower cv. 'Pusa Snowball K-1' - Bana, M.L.; Kaushik, R.A.; Bana, R.S.; Dhakar, M.K. (Annals of Agricultural Research, 2014)
A field experiment was undertaken at Rajasthan College of Agriculture, Udaipur to evaluate the effect of different weed management practices on weed dynamics in cauliflower (Brassica oleracea var. botrytis L.) cv. 'Pusa Snowball K-1' during the year 2009-10. The treatments comprising ten weed control methods were weedy check, two hand weedings i.e. 35 and 60 days after transplanting (DAT), black plastic mulch, rice straw mulch and three herbicides (fluchloralin at 1.5 kg/ha, pendimethalin at 1.5 kg/ha and alachlor at 2 kg/ha) alone and in combination with one hand weeding at 35 DAT. Among the different treatments the black plastic mulch treated plot showed excellent weed control. The growth (plant height, spread and number of leaves), quality (compactness, color and per cent protein content of curd) and yield were also higher under black plastic mulch but it was not significantly different with rice straw mulch. Among the herbicides pendimethalin in combination with one hand weeding was found most effective. The results further revealed that the rice straw mulch gave highest benefit:cost ratio of 3.48: 1.